2020
DOI: 10.3390/f11010067
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Extrafloral Nectar in Boreal Forest Ecosystems under Climate Change

Abstract: Carbohydrate-rich extrafloral nectar (EFN) is produced in nectaries on the leaves, stipules, and stems of plants and provides a significant energy source for ants and other plant mutualists outside of the flowering period. Our review of literature on EFN indicates that only a few forest plant species in cool boreal environments bear EFN-producing nectaries and that EFN production in many boreal and subarctic plant species is poorly studied. Boreal forest, the world’s largest land biome, is dominated by conifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 173 publications
0
7
0
Order By: Relevance
“…All these findings underline the value of fern nectar to any opportunistic insect or mollusk, and we must assume that in nature there must be a wide array of animals searching for and feeding on fern nectar, even if such interaction would not necessarily represent a mutualistic relationship. In boreal forests, EFN are relatively rare, and Harppolainen et al (2020) suggested that EFN‐bearing plants might be outcompeted by aphid honeydew as the main carbohydrate source for ants. On the contrary, we could imagine that EFN have especially been developed in the tropics to counteract honeydew‐producing aphids by distracting their ants, and by offering them an alternative nectar source as suggested by Becerra and Venable (1989), but this hypothesis needs further investigation in ferns.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings underline the value of fern nectar to any opportunistic insect or mollusk, and we must assume that in nature there must be a wide array of animals searching for and feeding on fern nectar, even if such interaction would not necessarily represent a mutualistic relationship. In boreal forests, EFN are relatively rare, and Harppolainen et al (2020) suggested that EFN‐bearing plants might be outcompeted by aphid honeydew as the main carbohydrate source for ants. On the contrary, we could imagine that EFN have especially been developed in the tropics to counteract honeydew‐producing aphids by distracting their ants, and by offering them an alternative nectar source as suggested by Becerra and Venable (1989), but this hypothesis needs further investigation in ferns.…”
Section: Discussionmentioning
confidence: 99%
“…The results of HB 2 show that growth traits are more affected by the environment, and tree height is more affected by the environment than DBH(0.13<0.28). The Type-B genetic correlation coefficient results showed that both tree height and DBH traits were affected by G×E (rb <0.7), and tree height was more affected.…”
Section: Heritabilityandtype B Correlationandgenetic Gain Of Selected Genotypesmentioning
confidence: 99%
“…They are essential for human because they give fresh air, nutrition, habitat, energy, and a source of income for the various people that rely on forest. Forests are habitat to 80% of the planet's species diversity and provide all of the fundamental needs for nearby human habitation [1][2][3][4] . Poplar (Populus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…The responses can result in a reduction in the attractiveness of trees to herbivorous insects [57, 58, 66 •]. Another study found that exposure to HIPVs enhances the production of extrafloral nectar in hybrid aspen saplings [62], which may attract more natural enemies of herbivorous insects [77][78][79]. A recent observation has shown that potted pine saplings exposed to neighboring plants damaged by pine weevils (Hylobius abietis) responded to subsequent herbivory by inducing higher emissions of volatile terpenes and were fourfold less fed upon by weevils [67 • ].…”
Section: Mechanisms Of Aboveground Bvoc-mediated Communication In Treesmentioning
confidence: 99%